Protein and amino acids of breast milk from Thai mothers - B. Chavalittamrong (2018)
This study evaluates the effects of prolonged lactation on the quantity of protein and pattern of amino acids in breast milk of 135 Thai women at various times of lactation (from 0 to 270 days postpartum). Breast milk samples were collected approximately 3 hours after nursing at various times during 1978. Total nitrogen, tryptophan and amino acids were respectively analyzed by the methods of Williams, Lorenzo-Andreu and Frandsen and Matheson, and Hitachi Perkin-Elmer Model KLA3B amino acid analyzer. Protein level in breast milk was highest during the 1st week (1.56%) and decreased steadily with time until a level of 0.60% during the period of 180 to 270 days, after which protein content appeared to increase. Ratio of essential to nonessential amino acids was constant throughout the study. Protein or amino acid levels during lactation were not significantly affected by maternal age and parity, although maternal age, parity and socioeconomic factors had been known to affect total milk secretion. Amino acid levels in this study were generally similar to reported values from American and Scottish women, although methionine, valine and tyrosine were lower and tryptophan and lysine were higher. Although breast milk has a nutritional value of the highest quality, it can be argued that the need for supplemental feeding may still occur earlier in life than is often realized. A discussion of the FAO/WHO standards for protein allowances suggests that infants up to 3 months of age require approximately 2 or more g of milk protein per kg daily, while children 60 to 12 months of age require about 1.5 g/kg/daily. Considering that protein content of Thai breast milk is about 0.9% after 3 months of lactation, it is estimated that 1250 ml of milk are needed to supply the protein needs of a 3-month old child, and 950 ml would be insufficient (average daily production of milk varies from 850 ml to 1200 ml). Many Thai and other women who are exclusively breastfeeding may find it difficult to provide the protein needs of their infants, unless supplemental feeding is carried out.